Analisis Perbandingan Kinerja Keuangan PT Bank Mandiri Tbk dengan PT Bank Rakyat Indonesia Tbk - Fazhar Sumantri; Dwi Apriliani (MONETER - JURNAL AKUNTANSI DAN KEUANGAN, 2018)
ABSTRACT - PT Bank Mandiri Tbk. with PT Bank Rakyat Indonesia Tbk. are the two banks that consistently hold the largest assets in Indonesia, for the community, especially the business people, of course these two banks are an attraction to invest their funds. Before entrusting the funds, it is important for the public to know which bank performs best before entrusting the funds. This study aims to compare the financial performance between PT Bank Mandiri Tbk. with PT Bank Rakyat Indonesia Tbk. the period of 2013-2017 measured in the financial ratios of LDR (X1), ROA (X2), ROE (X3), BOPO (X4), CAR (X5) and DER (X6) using One Way Anova test at the 5% or 0.05 significance level. The results of this study based on the value of each ratio, the financial performance of PT Bank Rakyat Indonesia Tbk. is superior to PT Bank Mandiri Tbk. if measured using ROA (X2), ROE (X3), CAR (X5), but PT Bank Rakyat Indonesia Tbk. has a higher risk in managing its operational expenses to its revenue and liquidity management because the credit value is greater than its liquidity value. Based on the One Way Anova test simultaneously in this study it can be concluded that there are significant financial performance differences between PT Bank Mandiri Tbk. with PT Bank Rakyat Indonesia Tbk., while based on One Way Anova test partially in this research can be concluded that ROA (X2) has difference of financial performance with significance value 0.009 <0.05.Keywords: Financial Ratios, Financial Performance Comparisons